Modified proton exchange membrane as well as preparation method and application thereof

By coating the platinum carbon catalyst on the surface of the base film of the proton exchange membrane to form a cathode and anode layer with a specific mass ratio, the existing membrane reaction rate and hydrogen permeation problems are solved, and the performance and hydrogen conversion of the fuel cell are improved.

CN119170810APending Publication Date: 2024-12-20STATE GRID INTELLIGENCE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411299430.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

During use, the existing proton exchange membrane has low reaction rate, low hydrogen conversion rate and easy to cause hydrogen permeation, resulting in poor fuel cell performance.

Method used

The surface of the base film is coated with perfluorosulfonic acid resin slurry containing platinum carbon catalyst to form a cathode and anode layer, and control the mass ratio of platinum to sulfonic acid group to be within the range of 1:500 to 1500, reduce porosity and improve the reaction rate and reduce gas permeation.

Benefits of technology

The reaction rate and hydrogen conversion rate of the proton exchange membrane are improved, gas permeability is reduced, and the performance and efficiency of fuel cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170810A_ABST
    Figure CN119170810A_ABST
Patent Text Reader

Abstract

The invention provides a modified proton exchange membrane as well as a preparation method and application thereof, and the preparation method comprises the following steps: (1) mixing and dispersing a platinum-carbon catalyst and a perfluorosulfonic acid resin solution to obtain slurry; and (2) respectively coating two surfaces of a base membrane with the slurry obtained in the step (1) to obtain the modified proton exchange membrane, in the slurry in the step (1), the mass ratio of platinum to sulfonic groups is 1: (500-1500). According to the modified proton exchange membrane obtained by the preparation method, the reaction potential can be reduced, the resistance can be reduced, the reaction path can be shortened, and the reaction rate can be increased; the proton conduction efficiency is improved; and the permeation of gas into the proton exchange membrane from the two sides of the electrode can be reduced, the conversion rate of the gas is improved, and the battery performance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a modified proton exchange membrane and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane fuel cell is a device that uses hydrogen as fuel and air as oxidant, and directly converts the chemical energy in the fuel and oxidant into electrical energy through electrochemical reaction. Proton exchange membrane fuel cell has high energy conversion efficiency; the emission is water and water vapor, which is zero pollution; there is no mechanical vibration, low noise and low heat radiation; therefore, it has good application prospects.

[0003] The core component of proton exchange membrane fuel cells is the membrane electrode; and one of the key components of the membrane electrode is the proton exchange membrane, which plays a dual role in fuel cells. One is to transfer the protons formed near the catalyst from the hydrogen electrode to the oxygen electrode, and the other is to act as an isolation membrane to separate the two-electrode reaction gases. The proton exchange membrane is the technical key of the fuel cell, and its performance directly affects the working performance of the fuel cell.

[0004] Among them, perfluorosulfonic acid proton exchange membrane (Nafion membrane) is widely used in fuel cells because of its advantages such as good chemical and thermal stability, voltage reduction, high conductivity, high mechanical strength, and ability to be used under harsh conditions such as strong acid, strong alkali, strong oxidant media and high temperature.

[0005] However, in actual use, the existing proton exchange membrane has a low reaction rate due to the long ion reaction path and high resistance; and the existing proton exchange membrane has too large pores, which makes the membrane prone to hydrogen permeation during use under high pressure, resulting in a low hydrogen conversion rate and waste of hydrogen.

[0006] Therefore, developing a proton exchange membrane with a high reaction rate, which can reduce gas permeation, improve the conversion rate of hydrogen and the conductivity efficiency of protons, is an urgent problem to be solved in this field. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to provide a modified proton exchange membrane and a preparation method and application thereof. The modified proton exchange membrane obtained by the preparation method can reduce the reaction potential, increase the reaction rate, improve the proton conduction efficiency, and reduce the gas permeation from both sides of the electrode into the proton exchange membrane, thereby improving the gas conversion rate and improving the battery performance.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a modified proton exchange membrane, the preparation method comprising the following steps:

[0010] (1) mixing and dispersing a platinum-carbon catalyst and a perfluorosulfonic acid resin solution to obtain a slurry;

[0011] (2) The slurry obtained in step (1) is respectively coated on two surfaces of the base membrane to obtain the modified proton exchange membrane; in the slurry in step (1), the mass ratio of platinum to sulfonic acid group is 1:500 to 1500.

[0012] In the present invention, a perfluorosulfonic acid resin slurry containing a platinum-carbon catalyst is coated on the surface of a base membrane, a cathode layer and an anode layer are formed on the surface of the base membrane respectively, and the mass ratio of platinum to sulfonic acid group is controlled within the above range, so that platinum can be more evenly filled in the pores of the membrane, the porosity of the membrane is reduced, the reaction rate of the membrane is increased, the gas permeation is reduced, the hydrogen conversion rate is increased, and the waste of raw materials is avoided.

[0013] In the present invention, the mass ratio of platinum to sulfonic acid group is 1:500-1500, wherein the specific value of 500-1500 can be, for example, 500, 520, 540, 560, 580, 600, 620, 640, 660, 680, 700, 720, 740, 760, 780, 800, 820, 840, 860, 880, 900, 920, 950, 980, 1000, 1050, 1100, 1150, 1200, 1250, 1300, 1350, 1400, 1450, 1500, etc.

[0014] Preferably, the average particle size of the platinum-carbon catalyst in step (1) is 2 to 7 nm, for example, it can be 2 nm, 2.2 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.8 nm, 3 nm, 3.2 nm, 3.4 nm, 3.6 nm, 3.8 nm, 4 nm, 4.2 nm, 4.4 nm, 4.6 nm, 4.8 nm, 5 nm, 5.2 nm, 5.4 nm, 5.6 nm, 5.8 nm, 6 nm, 6.2 nm, 6.4 nm, 6.6 nm, 6.8 nm, 7 nm, etc., preferably 2.8 to 7 nm.

[0015] In the present invention, the particle size refers to the particle size of platinum; if the particle size is too small, it cannot be filled into the pores of the membrane, which easily leads to gas penetration and poor catalytic effect; if the particle size is too large, it is easy to cause membrane rupture, and at the same time, insufficient contact with hydrogen leads to reduced catalytic effect.

[0016] Preferably, the specific surface area of ​​the metal of the platinum-carbon catalyst is 50 to 100 m 2 / g, for example, 50m 2 / g, 52m 2 / g, 54m 2 / g, 55m2 / g, 56m 2 / g, 58m 2 / g, 60m 2 / g, 62m 2 / g, 64m 2 / g, 66m 2 / g, 68m 2 / g, 70m 2 / g, 72m 2 / g, 74m 2 / g, 76m 2 / g, 78m 2 / g, 80m 2 / g, 82m 2 / g, 84m 2 / g, 86m 2 / g, 88m 2 / g, 90m 2 / g, 92m 2 / g, 94m 2 / g, 96m 2 / g, 98m 2 / g、100m 2 / g, etc.; more preferably 55 to 85 m 2 / g.

[0017] Preferably, the step (1) further includes a step of grinding the platinum-carbon catalyst before the mixing and dispersing.

[0018] Preferably, the grinding time is 20 to 120 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 50 min, 60 min, 70 min, 80 min, 100 min, 120 min, etc.

[0019] In the present invention, the grinding equipment includes but is not limited to a planetary ball mill; the purpose of grinding is not only to obtain a platinum-carbon catalyst with a specific particle size, but also to make the platinum-carbon catalyst evenly dispersed.

[0020] Preferably, the platinum content in the platinum-carbon catalyst in step (1) is 40-70%, for example, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc.

[0021] In the present invention, the platinum content refers to the mass percentage.

[0022] Preferably, the solid content of the perfluorosulfonic acid resin solution in step (1) is 10-30%, for example, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, etc.

[0023] In the present invention, the perfluorosulfonic acid resin solution is a Nafion solution. The perfluorosulfonic acid resin is a type of copolymer consisting of a carbon fluorine main chain and a considerable number of perfluoropolyether side chains with ion exchange function; its structure is as follows:

[0024]

[0025] Wherein, X is an ion exchange group, which is -SO3H or -SO3Na, and the -SO3H type perfluorosulfonic acid ion exchange membrane is usually called a perfluorosulfonic acid proton exchange membrane; since the sulfonic acid group has hydrophilic properties, in the presence of water or other polar solvents, the sulfonic acid group will dissociate and protonate the solvent molecules, thereby forming a solvated SO3 - Hydrophilic phase including ions, SO3 - The ions are bound to the hydrophobic skeleton through the side chains, so the membrane can swell in the solution, the membrane structure becomes loose, and many fine curved channels are formed. + 、Na + exchange and pass through the membrane. - The position is fixed with repulsion Cl - and OH - function, so that they cannot pass through the ion membrane.

[0026] Preferably, the mixed dispersion in step (1) includes a first dispersion and a second dispersion.

[0027] Preferably, the first dispersing is performed under ultrasonic conditions.

[0028] Preferably, the first dispersion time is 1 to 5 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc.

[0029] Preferably, the second dispersing is performed in an oxygen-free environment.

[0030] Preferably, the temperature of the second dispersion is ≤4°C, for example, it can be 0°C, 1°C, 2°C, 3°C, 4°C, etc.; the time is 4 to 10 hours, for example, it can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.

[0031] Preferably, the coating method in step (2) comprises spraying.

[0032] Preferably, the spraying comprises ultrasonic spraying.

[0033] In the present invention, the preparation method adopts ultrasonic spraying, during which the solvent will volatilize, and no drying is required, thereby avoiding the evaporation of water in the membrane electrode due to excessively high temperature or excessively long drying time, which would have an adverse effect on the membrane electrode.

[0034] Preferably, the base membrane comprises an electrolyte membrane.

[0035] In the present invention, the electrolyte membrane includes a perfluorosulfonic acid proton exchange membrane (Nafion membrane).

[0036] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0037] (1) grinding a platinum carbon catalyst having an average particle size of 2 to 7 nm for 20 to 120 minutes, mixing and dispersing the catalyst with a perfluorosulfonic acid resin solution under ultrasonic conditions for 1 to 5 hours, and then continuing to stir and disperse the catalyst in an oxygen-free environment at a temperature of ≤4° C. for 4 to 10 hours to obtain a slurry;

[0038] (2) The slurry obtained in step (1) is coated on two surfaces of the base membrane respectively to obtain the modified proton exchange membrane; the coating method includes ultrasonic spraying.

[0039] In a second aspect, the present invention provides a modified proton exchange membrane, which is prepared according to the preparation method described in the first aspect.

[0040] In a third aspect, the present invention provides a membrane electrode, comprising the modified proton exchange membrane according to the second aspect.

[0041] In a fourth aspect, the present invention provides a fuel cell, comprising the modified proton exchange membrane according to the second aspect or the membrane electrode according to the third aspect.

[0042] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The method for preparing a modified proton exchange membrane provided by the present invention can reduce the reaction potential, improve the reaction rate and proton conductivity of the proton exchange membrane, and can also reduce the permeation of the reaction gas, improve the gas conversion rate, avoid the waste of raw materials, obtain a proton exchange membrane with better performance, and thus improve the relevant performance of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1The current-voltage curve and power density curve of the fuel cell including the modified proton exchange membrane obtained by the preparation method provided in Examples 1 to 3 of the present invention are shown. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0047] The materials used in the present invention are as follows:

[0048] Platinum carbon catalyst 1: Beijing Nakaili Technology Co., Ltd. Premetek 60% platinum carbon catalyst (Vulcan XC-72 carrier), average particle size 4-5nm, metal specific surface area 60m 2 / g;

[0049] Platinum carbon catalyst 2: Beijing Nakaili Technology Co., Ltd. Premetek 50% platinum carbon catalyst (Vulcan XC-72 carrier), average particle size 3-4nm, metal specific surface area 65m 2 / g;

[0050] Platinum carbon catalyst 3: Beijing Nakaili Technology Co., Ltd. Premetek 60% platinum carbon catalyst (Ketjenblack carrier), average particle size 2.5nm, metal specific surface area 100m 2 / g;

[0051] Platinum carbon catalyst 4: Beijing Nakaili Technology Co., Ltd. Premetek 60% platinum carbon catalyst (Vulcan XC-72R carrier), average particle size 4-7nm, metal specific surface area 50m 2 / g;

[0052] Nafion solution: solid content 20%, DHx120 from Shandong Dongyue Future Hydrogen Energy Materials Co., Ltd.;

[0053] Nafion-based membrane: Shandong Dongyue Future Hydrogen Energy Materials Co., Ltd., perfluorosulfonic acid fuel cell proton membrane DMR100.

[0054] Example 1

[0055] This embodiment provides a modified proton exchange membrane and a preparation method thereof, the preparation method comprising:

[0056] (1) Platinum-carbon catalyst 1 was placed in a planetary ball mill and uniformly ground for 1 hour, with a mass ratio of platinum to sulfonic acid group of 1:1000, the ground platinum-carbon catalyst was mixed and dispersed with Nafion solution under ultrasonic conditions for 3 hours, and then continued to stir and disperse for 6 hours in an oxygen-free environment at a temperature of 0°C to obtain a slurry;

[0057] (2) The slurry obtained in step (1) is sprayed on the two surfaces of the Nafion base membrane respectively, and the spraying method is ultrasonic spraying, so as to obtain the modified proton exchange membrane; the spraying amount of the cathode layer is 0.25 mg / cm 2 ; The spraying amount of the anode layer is 0.1mg / cm 2 .

[0058] Example 2

[0059] This embodiment provides a modified proton exchange membrane and a preparation method thereof, the preparation method comprising:

[0060] (1) Platinum-carbon catalyst 2 was placed in a planetary ball mill and uniformly ground for 40 minutes, with a mass ratio of platinum to sulfonic acid group of 1:800. The ground platinum-carbon catalyst was mixed and dispersed with Nafion solution under ultrasonic conditions for 5 hours, and then continued to be stirred and dispersed for 4 hours in an oxygen-free environment at a temperature of 0°C to obtain a slurry;

[0061] (2) spraying the slurry obtained in step (1) onto the two surfaces of the Nafion base membrane respectively, using ultrasonic spraying to obtain a cathode layer and an anode layer respectively, i.e., obtaining the modified proton exchange membrane; the spraying amount of the cathode layer is 0.25 mg / cm 2 ; The spraying amount of the anode layer is 0.1mg / cm 2 .

[0062] Example 3

[0063] This embodiment provides a modified proton exchange membrane and a preparation method thereof, the preparation method comprising:

[0064] (1) Platinum-carbon catalyst 1 was placed in a planetary ball mill and uniformly ground for 20 minutes, with a mass ratio of platinum to sulfonic acid group of 1:1300, the ground platinum-carbon catalyst was mixed and dispersed with Nafion solution under ultrasonic conditions for 2 hours, and then continued to stir and disperse for 10 hours in an oxygen-free environment at a temperature of 0°C to obtain a slurry;

[0065] (2) spraying the slurry obtained in step (1) onto the two surfaces of the Nafion base membrane respectively, using ultrasonic spraying to obtain a cathode layer and an anode layer respectively, i.e., obtaining the modified proton exchange membrane; the spraying amount of the cathode layer is 0.25 mg / cm 2; The spraying amount of the anode layer is 0.1mg / cm 2 .

[0066] Example 4

[0067] This embodiment provides a modified proton exchange membrane and a preparation method thereof, which differs from Embodiment 1 only in that, in the preparation method, the platinum-carbon catalyst 1 is replaced with a platinum-carbon catalyst 3 of equal mass, and the other steps are the same as those in Embodiment 1.

[0068] Example 5

[0069] This embodiment provides a modified proton exchange membrane and a preparation method thereof, which differs from Embodiment 1 only in that, in the preparation method, the platinum-carbon catalyst 1 is replaced with a platinum-carbon catalyst 4 of equal mass, and the other steps are the same as those in Embodiment 1.

[0070] Comparative Example 1

[0071] This comparative example provides a modified proton exchange membrane and a preparation method thereof, which differs from Example 1 only in that, in the preparation method, step (1) reduces the amount of platinum-carbon catalyst so that the mass ratio of platinum to sulfonic acid group is 1:1600, and the other steps are the same as Example 1.

[0072] Comparative Example 2

[0073] This comparative example provides a modified proton exchange membrane and a preparation method thereof, which differs from Example 1 only in that, in the preparation method, step (1) increases the amount of platinum-carbon catalyst so that the mass ratio of platinum to sulfonic acid group is 1:400, and the other steps are the same as Example 1.

[0074] Performance Testing

[0075] The modified proton exchange membranes provided by Examples 1 to 5 and Comparative Examples 1 and 2 were assembled and activated into single cells according to GB / T 20042.5-2009 standard, and the corresponding polarization curve tests were performed; the test conditions were as follows: the cell temperature was 55° C., hydrogen was introduced into the anode at a stoichiometric ratio of 1.5, air was introduced into the cathode at a stoichiometric ratio of 6, the back pressure was 0.08 MPa, and the relative humidity of the anode and the cathode was 16% RH; after the cell was activated and the steady-state performance was stable, a polarization curve test was performed, the test voltage was gradually reduced from 1V to 0.3V, the change in current density was recorded, and the power density change curve was obtained based on the voltage and current density.

[0076] Among them, the current-voltage curve and power density curve of the fuel cell including the modified proton exchange membrane obtained by the preparation method provided in Examples 1 to 3 of the present invention are as follows: Figure 1 As shown by Figure 1It can be seen that the modified proton exchange membrane obtained by the preparation method provided by the present invention has a slower voltage drop, a flatter polarization curve and a higher power density as the current density increases, indicating that the resistance encountered in the electrode process is small, the reaction path is short, the reaction rate is fast, and the catalytic effect is good, so that the membrane electrode has good kinetic and electrochemical properties.

[0077] In addition, the current density is 700mA / cm 2 For example, the voltage and power density of the modified proton exchange membranes provided in Examples 4 to 5 and Comparative Examples 1 and 2 in the polarization curves were recorded. The results are shown in Table 1.

[0078] Table 1

[0079] Voltage (V) <![CDATA[Power density (mW / cm 2 )]]> Example 4 0.45 315 Example 5 0.42 294 Comparative Example 1 0.34 238 Comparative Example 2 0.38 266

[0080] As can be seen from Table 1, by comparing Example 1 with Comparative Examples 1 and 2, in the present invention, the mass ratio of platinum to sulfonic acid group is not within a specific range, the resistance in the electrode process is large, the reaction path is long, the reaction rate of the modified proton exchange membrane is slow, and at the same current density, the voltage and power density are low, and the kinetic performance and electrochemical performance of the membrane electrode are poor.

[0081] In summary, the preparation method of the modified proton exchange membrane provided by the present invention can improve the reaction rate and proton conductivity of the proton exchange membrane by coating a perfluorosulfonic acid resin slurry containing a platinum-carbon catalyst on the surface of the base membrane, forming a cathode layer and an anode layer on the surface of the base membrane respectively, and controlling the mass ratio of platinum to sulfonic acid groups within a specific range; and can also reduce the permeation of the reaction gas, improve the gas conversion rate, avoid the waste of raw materials, obtain a proton exchange membrane with better performance, and thereby improve the relevant performance of the fuel cell.

[0082] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a modified proton exchange membrane, characterized in that: The preparation method comprises the following steps: (1) mixing and dispersing a platinum-carbon catalyst and a perfluorosulfonic acid resin solution to obtain a slurry; (2) applying the slurry obtained in step (1) to two surfaces of the base membrane respectively to obtain the modified proton exchange membrane; In the slurry of step (1), the mass ratio of platinum to sulfonic acid group is 1:500-1500.

2. The preparation method according to claim 1, characterized in that: The average particle size of the platinum-carbon catalyst in step (1) is 2 to 7 nm, preferably 2.8 to 7 nm; Preferably, the specific surface area of ​​the metal of the platinum-carbon catalyst is 50 to 100 m 2 / g, more preferably 55 to 85 m 2 / g; Preferably, the step (1) further comprises the step of grinding the platinum-carbon catalyst before the mixing and dispersing; Preferably, the grinding time is 20 to 120 minutes.

3. The preparation method according to claim 1 or 2, characterized in that: The platinum content of the platinum-carbon catalyst in step (1) is 40-70%; Preferably, the solid content of the perfluorosulfonic acid resin solution in step (1) is 10-30%.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The mixed dispersion in step (1) includes a first dispersion and a second dispersion; Preferably, the first dispersing is performed under ultrasonic conditions; Preferably, the first dispersion time is 1 to 5 hours; Preferably, the second dispersion is performed in an oxygen-free environment; Preferably, the temperature of the second dispersion is ≤4° C. and the time is 4 to 10 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The coating method in step (2) includes spraying; Preferably, the spraying comprises ultrasonic spraying.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The base film includes an electrolyte membrane.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) grinding a platinum carbon catalyst having an average particle size of 2 to 7 nm for 20 to 120 minutes, mixing and dispersing the catalyst with a perfluorosulfonic acid resin solution under ultrasonic conditions for 1 to 5 hours, and then continuing to stir and disperse the catalyst in an oxygen-free environment at a temperature of ≤4° C. for 4 to 10 hours to obtain a slurry; (2) The slurry obtained in step (1) is coated on two surfaces of the base membrane respectively to obtain the modified proton exchange membrane; the coating method includes ultrasonic spraying.

8. A modified proton exchange membrane, characterized in that: The modified proton exchange membrane is prepared according to the preparation method according to any one of claims 1 to 7.

9. A membrane electrode, characterized in that: The membrane electrode comprises the modified proton exchange membrane according to claim 8.

10. A fuel cell, characterized in that: The fuel cell comprises the modified proton exchange membrane according to claim 8 or the membrane electrode according to claim 9.